A Hacker's Mind. - Zuckerman, Ethan (Prospect)
Schneier sees everything from tax avoidance to electoral gerrymandering as hacking and suggests that the hackers we should worry about are not teenagers in hoodies, but accountants, lawyers and lobbyists in suits. Those developers created the internet of ecommerce and online work and play, and Schneier went on to write highly readable books explaining the weaknesses and vulnerabilities of the systems they built. By Bruce Schneier Thirty years ago, Bruce Schneier wrote a book on cryptography - the codes and security techniques that protect transactions and activities online - that trained a generation of software developers.